Semiotics of Vaccination Adver-tising in Media Discourse - Yu. V. Donskova; A. D. Kurilova; O. A. Makhno (Научный диалог, 2023)
The aim of the article is to analyze the verbal and visual means in advertising COVID-19 vaccination. The task is to examine the peculiarities of semiotics in vaccination advertising based on campaigns from different countries around the world, identify successful advertising strategies, and discover the reasons for communicative failures. The study analyzes the techniques of combining visual and verbal narratives in creolized advertising texts. It emphasizes that it is the visual narrative that appeals to the subconscious, which often contributes to the recipient’s necessary post-communicative action. The article examines the tactics of argumentation used in vaccination advertising (including appeals to authority, values such as health, love, freedom, etc.), studies the semiotics of the visual elements involved in argumentation. The article also analyzes the semiotics of color signals in advertising discourse, revealing their influence on the recipient’s subconscious. Examples of using semantic signs taken from other semantic domains, such as election campaigns and road sign systems, are separately considered in vaccination campaigns. The creativity of these techniques is noted, but the danger of visual disconnect with slogans and communicative failure is also indicated. The conclusion is drawn that advertising appealing to positive feelings of social responsibility, comfort, and well-being is more effective than advertising using threat-based argumentation.